Statistics of the Interplanetary Magnetic Field from 0.1 to 30 au. II. Dynamical Variability - Jiutong Zhao; Shan Wang; Weijie Sun; Xingyu Zhu; Chuanpeng Hou; Qiugang Zong; Jiansen He; Xuzhi Zhou; Chao Yue; Liu Yang; Daniel Heyner (The Astrophysical Journal)
The interplanetary magnetic field (IMF) governs the coupling between the solar wind and planetary magnetospheres through a series of complex interactions. However, it is challenging to simultaneously measure both the upstream IMF conditions and magnetospheric activity in situ. A common alternative approach is to utilize recent upstream measurements obtained before the spacecraft crosses the bow shock. To assess the validity of this method, we examine the temporal variability of the IMF using spacecraft magnetic field data from multiple space missions. Our analysis reveals that the autocorrelation function employed to measure IMF temporal variability is significantly influenced by the heliocentric distance and the solar cycle. Notably, the temporal variability of each magnetic field component varies, with the component aligned with the Parker spiral direction exhibiting weaker temporal variability than those perpendicular to it. Furthermore, the autocorrelation coefficients decay slower in the outer heliosphere, possibly due to the expansion, deformation, or merging of solar wind flux tubes. Nevertheless, considering planetary bow shocks and spacecraft travel time from the solar wind to the inner planetary magnetosphere (e.g., ∼2 hrs for Mars and ∼30 days for Jupiter), it is more feasible to estimate the upstream IMF conditions for the inner planetary magnetosphere than for the outer ones. Our study unravels the long-term evolution of the solar wind magnetic field and the consequence of the flux tube interaction. These results can also benefit the investigation of the solar wind–planetary magnetosphere coupling process by providing a more robust analysis of the upstream condition.